From "change" to gridlock? The US midterm elections 2010 - Stormy-Annika Mildner; Johannes Thimm; Henriette Rytz (Stiftung Wissenschaft und Politik (SWP), 2010)
The decisive Republican victory in the election to the House of Representatives ended a brief period of »unified government« in the United States - the rare situation in which one party controls both the US Congress and the White House. While the new balance of power might result in political gridlock, it could also rouse Republicans from their legislative obstructionism. As the majority party, they now bear the responsibility to generate constructive solutions. However, since the next presidential election campaign is expected to start in late 2011, this window of opportunity might not be open for long
Keywords: 320